Moderasi NPF terhadap Intervensi BOPO dan CAR pada Kinerja Keuangan Bank Syariah di Indnesia 2019-2021 - Toha Barizi; Rifky Fatoni; Zuni Fitrowati; Umrotul Khasanah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The goal of this research is to look into the impact of Operating Costs on Operating Income (BOPO) and Capital Adequacy Ratio (CAR) on the Financial Performance of Islamic Commercial Banks, which is measured using one of the profitability ratio indicators, Return on Assets (ROA). This study employs a quantitative approach by employing explanatory research, which tries to examine the theories and hypotheses that exist in this study in order to determine whether they strengthen or weaken earlier theories and hypotheses. The study relied on secondary data, specifically information gathered from the ojk.ac.id website. This research uses monthly time series data from the Financial Services Authority from 2019 to 2021, with a sample size of 26 months. Multiple linear regression and moderated regression analysis were employed in this study's regression model (MRA). The findings of this study revealed that BOPO had a considerable impact on ROA, although CAR had no such impact, and that NPF, as a moderating variable, was able to moderate the impact of BOPO and CAR on ROA.